2018
DOI: 10.6007/ijarbss/v8-i7/4387
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Entrepreneurship Orientation, Government Support and Internationalization on Malaysian SMEs Performance

Abstract: Prior studies on small and medium sized enterprises (SMEs) in Malaysia have focused on performance with inconclusive results. This paper contributes to the literature by examining variation in performance resulting from the synergistic role of entrepreneurial orientation, government support and internalization. It primarily explores three main industries: manufacturing, service and agriculture, generating data from 218 self-administered questionnaires. Using the Partial Least Squares (PLS) regression in testin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 41 publications
3
6
0
Order By: Relevance
“…SMEs should concentrate on how to deal with issues such as entrepreneurial competencies, innovation, and the failure to compete aggressively (i.e. Ismail and Zakaria, 2018;Tehseen et al, 2019). Drawing on the previous research findings, this study asks the research questions as follows:…”
Section: Introductionmentioning
confidence: 99%
“…SMEs should concentrate on how to deal with issues such as entrepreneurial competencies, innovation, and the failure to compete aggressively (i.e. Ismail and Zakaria, 2018;Tehseen et al, 2019). Drawing on the previous research findings, this study asks the research questions as follows:…”
Section: Introductionmentioning
confidence: 99%
“…The literature reveals that Malaysian SMEs are not involved in the international trade as much as expected (Ismail and Zakaria, 2018). The reason is the confined entrepreneurial directions of SMEs in this country.…”
Section: Business Management and Strategymentioning
confidence: 82%
“…What worse is, reports have suggested that Malaysian SMEs apparently refuse to be risk-takers, insufficient innovativeness, and are not ready for vigorous competition (Ismail and Zakaria, 2018). Radzi et al (2017) concluded in their study that due to technology incompetence among Malaysian SMEs, caused them to produce low performance in business.…”
Section: Smes' Readiness Towards Industry 40mentioning
confidence: 99%
“…This particular account is definitely of grave concern since the majority of the market-leading industrial companies have already jumped on the bandwagon, forecasting and making a prognosis of risk-benefit assessment upon embracing Industry 4.0.Nevertheless, the vigilant approach conducted by some local SMEs is not entirely null and void asDalenogare et al (2018) contended that it is a relevant measure since the conception of Industry 4.0 is rather brand new, comprising a broad range of different elements and varying components which are yet to be comprehended and discovered. Hence, due to that, it would be sensible for any enterprise to be cautious of undertaking measures as the already existing expertise and experience would not suffice to face the uncertainties of the actual implications and contributions of Industry 4.0, which generally pertains to technologies in the context of evolving nations.What worse is, reports have suggested that Malaysian SMEs apparently refuse to be risk-takers, insufficient innovativeness, and are not ready for vigorous competition(Ismail and Zakaria, 2018) Radzi et al (2017). concluded in their study that due to technology incompetence among Malaysian SMEs, caused them to produce low performance in business.…”
mentioning
confidence: 99%